German economy: Upward trend continues despite Brexit vote's dampening effect - Ferdinand Fichtner; Karl Brenke; Marius Clemens; Simon Junker; Claus Michelsen; Maximilian Podstawski; Thore Schlaak; Kristina van Deuverden (DIW Economic Bulletin, 2016)
The German economy has been growing significantly recently, also due to strong foreign trade, and will experience a powerful increase of 1.9 percent in 2016. In the coming quarters, the drag of the Brexit decision should become noticeable. This will dampen the year-on-year growth rate in 2017 to 1.0 percent, alongside somewhat weaker private consumption dynamics. From the second half of 2017 onward, industry will start benefitting once again from a more dynamic development in key foreign markets, and in 2018, the German economy is expected to grow by 1.6 percent. Throughout the forecast period, the increase in employment should continue, and private consumption will contribute to growth-albeit at a somewhat slower pace. The unemployment rate should continue to drop: from 6.1 and 5.9 percent in 2016 and 2017 respectively to 5.8 percent by 2018. At 0.5 percent, inflation is low again this year, but at one-and-a-half percent, it will be higher in both 2017 and 2018. Corporate investment remains weak and won't start picking up momentum until the end of next year, in view of accelerating global growth dynamics. The government surplus is expected to increase to 27 billion euros this year; however, the surplus will be smaller in the coming years, at 14 billion euros in 2017 and 16 billion euros in 2018.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook